2017
DOI: 10.14716/ijtech.v8i1.2734
|View full text |Cite
|
Sign up to set email alerts
|

Wire Rope Flexural Bonded Strengthening System on RC-Beams: A Finite Element Simulation

Abstract: We conducted a finite element simulation by using a computer program, ATENA, to verify the behavior of T-section reinforced concrete beams strengthened by bonded wire ropes in the negative moment region with a pretensioned initial prestressing force; we compared this behavior with that in experimental tests. The simulation was performed on five models consisting of one unstrengthened beam and beams strengthened by wire ropes with initial prestressing forces of 0%, 10%, 20%, and 30%. We found that the capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…This type of behavior has also been reported elsewhere for RC beams and posttensions continuous tendons. 25,26 Cracking patterns obtained using ATENA (see Figure 35) also find a close agreement with those observed experimentally (see Figure 36). In general, ATENA was able to predict peak load and its corresponding mid-span deflection, crack patterns, and failure mode of FPP girder with a good accuracy.…”
Section: Finite Element Analysis Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This type of behavior has also been reported elsewhere for RC beams and posttensions continuous tendons. 25,26 Cracking patterns obtained using ATENA (see Figure 35) also find a close agreement with those observed experimentally (see Figure 36). In general, ATENA was able to predict peak load and its corresponding mid-span deflection, crack patterns, and failure mode of FPP girder with a good accuracy.…”
Section: Finite Element Analysis Resultssupporting
confidence: 80%
“…A slight lower peak load was observed for analytical prediction in comparison to the experimental curve which can be acceptable given that the model did not overestimate the peak load. This type of behavior has also been reported elsewhere for RC beams and posttensions continuous tendons 25,26 . Cracking patterns obtained using ATENA (see Figure 35) also find a close agreement with those observed experimentally (see Figure 36).…”
Section: Finite Element Analysissupporting
confidence: 89%
“…The service life of reinforced concrete structures decreases. To repair the decreasing capacity load of the beam, it can be strengthened by using wire rope [13].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed that the flexural strength in the region of positive moment increased and had a ratio of 1.86 [12]. Optimisation via an initial pre-stressing force on the bonded strengthening and two pieces of steel wire rope shows that an initial pre-stressing force of 20% gave the highest flexural strength improvement [13,14]. Another method involved the addition of steel rebars in a compression block for reinforced concrete Tbeams which were strengthened with steel wire ropes in the region of negative moment; this method resulted in an increase in flexural strength and had a ratio of 2.93 [15].…”
Section: Introductionmentioning
confidence: 99%